Bulgaria's energy security in the context of energy dependence on the import of oil products - Diana Eftimova (CES Working Papers, 2018)
Over the years Bulgaria has remained strongly dependent on its import of oil products mainly due to the lack of oil resources on its territory. This import dependence poses a significant risk for the country's energy security. In this research we analyse Bulgaria's energy security in terms of its dependence on the import of oil products. For the purposes of this research on the energy dependence we estimated the degree of Bulgaria's dependence on the import of oil products it needs, as well as the degree of import diversification in terms of the number of suppliers and the diversification index. The results show an interesting trend – despite the large number of suppliers, the diversification index remains at levels that pose high risk for the energy security of the country.
Keywords: 330; Bulgaria's energy security; energy; import dependence; diversification index; oil products